A trial to generalise evaluation of key driving factors of port-city waterfront development. (8th April 2020) - Suthiwartnarueput, Kamonchanok; Lee, Paul Tae-Woo; Lin, Cheng-Wei; Visamitanan, Krisana; Yang, Zaili; Ng, Adolf K.Y.
This paper investigates the key successful factors in waterfront port development (WPD). Consistent fuzzy preference relation (CFPR), with the combination of the preference ranking organisation methods for enrichment evaluation (PROMETHEE), is applied to six ports, namely Busan, Incheon Inner Port, Bangkok, Kaohsiung, Montreal and Liverpool. The latter technique evaluates the performance of WPD among the studied cases, while the former draws the key successful factors (KSFs) of the selected ports. To draw meaningful comparison with the test results from past research, this paper takes the same evaluation hierarchy in the questionnaire form in Lee et al. (2016). With a further validity of the previous findings in WPD studies, this paper does not only provide insight on exploring the generalisation of KSFs in WPD in a longitude manner, but also contributes to the literature of WPD and port-city interplays.